Removed to the Signifier: Utopia in Stephen Graham Jones's The Bird Is Gone: A Monograph Manifesto (2003). Issue 1 (10th April 2018) - Baudemann, Kristina
This article deals with the speculative utopia in Stephen Graham Jones's the bird is gone: amonograph manifesto (2003 ). Arguing that Jones foregrounds the utopian traits of US-American colonialism, specifically of Andrew Jackson's Indian Removal policy, I explore the conditions of a postcolonial—or rather decolonial—Indigenous-centered utopia. As exemplified in Jones'smonograph manifesto, the latter does not consist in setting Indigenous communities back to a pre-colonial default state because colonialism is not reversible. The utopian space is instead moved from the level of representation to the level of signifiers, where it exists in a space of possibility opens up in the continuous shift of meaning/signifieds and humorous play with readerly expectations. As such, Jones's work not only dislodges and subverts, but also renews literary utopia. In its focus on colonial history and textual experimentation, bird demonstrates that utopia can serve as both a space for settler colonial exploitation and a tool kit for imagining a decolonial and Indigenous-centered future.